P I – 1–5 Association between air pollution and severity of rhinitis in two european cohorts. (18th March 2018) - Burte, Emilie; Leynaert, Bénédicte; Künzli, Nino; Siroux, Valérie; Jarvis, Deborah; Nadif, Rachel; Jacquemin, Bénédicte
Abstract : Background/aim: Little is known about the effects of outdoor air pollution on severity of rhinitis. The objective is to assess the association between modelled PM10, PM2.5 and NO2 concentrations and severity of rhinitis in two multicenter European cohorts on respiratory health (EGEA and ECRHS). Methods: 1603 adults with data on air pollution and on severity of at least one rhinitis symptom were included. Annual exposure to NO2, PM10 and PM2.5 was estimated at participants' residential address using land use regression models thanks to the ESCAPE project. Severity of rhinitis was defined in two ways: according to the importance of the disturbance due to four symptoms of rhinitis (runny nose, blocked nose, sneezing and itchy nose) categorised in 3 groups: no (reference), mild or high severity, using an overall score of severity including disturbances to all symptoms, varying from 0 to 12. Polytomous logistic or linear regression was used, and the city was further included as a random effect. Adjusted odds ratio are presented for an increase of 10 µg.m −3 of NO2 and 5 µg.m −3 of PM2.5 . Results: The 1603 adults (mean age=52.5 years, 45% men, 73% from ECRHS) from 17 cities had a median[Q1-Q3] score of severity of 4[2–6]. Exposure to air pollution was associated with an increased score of severity of rhinitis (aOR[95% CI] for NO2 : 1.13 [1.03–1.25], for PM2.5 : 1.85 [1.47–2.33]). Exposure to NO2 was also associated with an increased severity of blocked nose (aOR for NO2 : 1.17 [1.06–1.30] for mild and 1.21 [1.10–1.33] for high severity) and similarly with runny nose, but not with itchy nose or sneezing. Exposure to PM2.5 or PM10 was associated with mild severity for blocked nose and with high severity for all symptoms (aOR for blocked nose for PM2.5 : 1.41 [1.06–1.88] for mild and 1.91 [1.46–2.51] for high severity). Similar results were found when considering city as a random effect. Conclusion: Severity of rhinitis and particularly blocked nose symptoms are associated with air pollution exposure.